Pseudouridine prevalence in Kaposi’s sarcoma–associated herpesvirus transcriptome reveals an essential mechanism for viral replication - Timothy J. Mottram; Katherine L. Harper; Elton J. R. Vasconcelos; Adrian Whitehouse (Proceedings of the National Academy of Sciences, 2025)
Pseudouridylation is a prevalent RNA modification occurring in transfer RNAs (tRNAs), ribosomal RNAs (rRNAs), small non-coding RNAs (snoRNAs), and has been most recently identified in mRNAs and lncRNAs. Emerging evidence suggests that this dynamic RNA modification is implicated in altering gene expression by regulating RNA stability, modulating translation elongation, and modifying amino acid substitution rates. However, the role of pseudouridylation in infection is poorly understood. Herein, we demonstrate that Kaposi’s sarcoma–associated herpesvirus (KSHV) manipulates the pseudouridylation pathway to enhance replication. We show that the pseudouridine synthases (PUS), PUS1, and PUS7 are essential for efficient KSHV lytic replication, supported by their redistribution to viral replication and transcription complexes. We present a comprehensive analysis of KSHV RNA pseudouridylation, revealing hundreds of modified RNAs at single-nucleotide resolution. Notably, we demonstrate that pseudouridylation of the KSHV-encoded polyadenylated nuclear RNA (PAN) plays a significant role in the expression of PAN RNA. These findings reveal an essential role of pseudouridine modification in the KSHV replication cycle.